2012
DOI: 10.4209/aaqr.2012.03.0070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Indoor-Air Bioaerosols in Southern Taiwan

Abstract: This study investigated indoor air quality (IAQ) at 39 public sites in southern Taiwan including hospitals, schools, office buildings, hypermarkets, libraries, railway stations, theaters, etc. Indoor air quality was preliminarily assessed using handy digital apparatus. Items detected include carbon dioxide (CO 2 ), carbon monoxide (CO), formaldehyde (HCHO), total volatile organic compounds (TVOCs), total bacteria counts (TBC), total fungi counts (TFC), PM 10 , PM 2.5 , ozone (O 3 ) and temperature. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 28 publications
2
29
1
Order By: Relevance
“…The indoor air quality in the hospital in this study is similar to one previous study included 8 hospitals in Taiwan (Hsu et al, 2012). We documented significant associations between questionnaire-reported SBS-related symptoms among medical workers and indoor air quality.…”
Section: Discussionsupporting
confidence: 76%
“…The indoor air quality in the hospital in this study is similar to one previous study included 8 hospitals in Taiwan (Hsu et al, 2012). We documented significant associations between questionnaire-reported SBS-related symptoms among medical workers and indoor air quality.…”
Section: Discussionsupporting
confidence: 76%
“…More information on both PM10 and PM2.5 comes from Asian countries ( Table 2). Two studies performed in Taiwan reported similar concentration ranges of PM10 (Wan et al 2011) and PM2.5 (Hsu et al 2012) to those in Portugal. In India and China, observed PM2.5 and PM10 in hospital environments were much higher than in Portugal (three to four times; Verma and Taneja 2011;Wang et al 2006a, b).…”
Section: Pm Concentrationsmentioning
confidence: 71%
“…In the studied hospital, more than 50 % of PM2.5 measured concentrations surpassed the 24-h guideline for ambient air which indicates the potential health risks of the exposed individuals. In addition, indoor particles can act as carrier for infectious microbes and microbial metabolites that may accumulate in the hospital environments (Hsu et al 2012), thus representing additional health risks (i.e., transmissions of airborne infectious diseases; Eames et al 2009;Tang et al 2011;Hsu et al 2012). …”
Section: Pm Concentrationsmentioning
confidence: 99%
“…Many chemical and biological aerosol contaminants influence indoor air quality as well as the quality of health (Hsu et al, 2012;Lee et al, 2012;Kram and Dmowska, 2013;Chen et al, 2015;Sidra et al, 2015). Bioaerosol contain many human pathogens including virus which is one of the biggest threats for human health.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the IAQ parameters including total bacteria counts, total fungi counts, carbon monoxide, carbon dioxide, particulate matter, ozone, and total volatile organic compounds (TVOCs) in workplaces, hospitals, transportation stations, department stores, supermarkets, and public buildings shall be met to the national standards in Taiwan (Hsu et al, 2012;Hsu et al, 2015), but airborne virus is not regulated yet. Airborne viruses and their vaccine are of particular interest due to their potentially adverse impact on human or animal health in the indoor environment.…”
Section: Introductionmentioning
confidence: 99%